Minimally invasive oesophagectomy with extended lymph node dissection and thoracic duct resection for early‐stage oesophageal squamous cell carcinoma. Issue 6 (20th February 2020) - Matsuda, S.; Kawakubo, H.; Takeuchi, H.; Hayashi, M.; Mayanagi, S.; Takemura, R.; Irino, T.; Fukuda, K.; Nakamura, R.; Wada, N.; Kitagawa, Y.
Abstract : Background: Oesophageal squamous cell carcinoma is an aggressive disease owing to early and widespread lymph node metastases. Multimodal therapy and radical surgery may improve prognosis. Few studies have investigated the efficacy of radical lymph node and thoracic duct resection. Methods: Patients with oesophageal squamous cell carcinoma who underwent transthoracic minimally invasive oesophagectomy (TMIE) for cancer at Keio University Hospital between January 2004 and December 2016 were selected. Between 2004 and 2008, TMIE was performed in the lateral decubitus position without thoracic duct resection (standard TMIE). From 2009 onwards, TMIE with extended lymph node and thoracic duct resection was introduced (extended TMIE). Demographics, co‐morbidity, number of retrieved lymph nodes, pathology, postoperative complications and recurrence‐free survival (RFS) were compared between groups. Results: Forty‐four patients underwent standard TMIE and 191 extended TMIE. There were no significant differences in clinical and pathological tumour stage or postoperative complications. The extended‐TMIE group had more lymph nodes removed at nodal stations 106recL and 112. Among patients with cT1 N0 disease, RFS was better in the extended‐TMIE group ( P < 0·001), whereas there was no difference in RFS between groups in patients with advanced disease. Conclusion: Extended TMIE including thoracic duct resection increased the number of lymph nodes retrieved and was associated with improved survival in patients with cT1 N0 oesophageal squamous cell carcinoma. Abstract : Transthoracic minimally invasive oesophagectomy with extended lymph node dissection and thoracic duct resection increased the number of lymph nodes (LNs) retrieved and improved survival in patients with oesophageal squamous cell carcinoma, especially those with cT1 N0 tumours. May be better for early stage disease